PENGABDIAN KEPADA MASYARAKAT: RUMAH SINGGAH SEHAT KREATIF MENOLAK CORONA - Sri Ratna Dewi; Desak i Putu Oki Lestar; A, A.G. Budhitresna; Luh Made Ayu Pradnyadari (Universitas Hindu Indonesia, 2023)
Yayasan Peduli Kanker Anak Bali is one of the non-profit foundations that helps children with cancer who need a temporary house while being treated at Sanglah Hospital. The priority problem faced by our partners is that children suffering from cancer have a higher risk of being infected with COVID-19, but masks and hand sanitizers are increasingly expensive and scarce, besides that the economy is also feeling increasingly sluggish due to the outbreak of this COVID-19 infection. This dedication activity aims to increase their knowledge of a clean and healthy life program, training in making hand sanitizers, and masks. The method used is the method of counseling, training and mentoring, and evaluation will be carried out to monitor the success of the activity. Based on the pre and posttest evaluation, an increase in knowledge of as much as 81% about a clean and healthy life program and all partners can make hand sanitizers and masks. Keywords: COVID-19, cancer foundation, hand sanitizers, masks